Latent class analysis suggests four distinct classes of complementary medicine users among women with breast cancer. Issue 1 (December 2015) - Strizich, Garrett; Gammon, Marilie; Jacobson, Judith; Wall, Melanie; Abrahamson, Page; Bradshaw, Patrick; Terry, Mary; Teitelbaum, Susan; Neugut, Alfred; Greenlee, Heather
Abstract Background Breast cancer patients commonly report using >1 form of complementary and alternative medicine (CAM). However, few studies have attempted to analyze predictors and outcomes of multiple CAM modalities. We sought to group breast cancer patients by clusters of type and intensity of complementary and alternative medicine (CAM) use following diagnosis. Methods Detailed CAM use following breast cancer diagnosis was assessed in 2002–2003 among 764 female residents of Long Island, New York diagnosed with breast cancer in 1996–1997. Latent class analysis (LCA) was applied to CAM modalities while taking into account frequency and intensities. Results Four distinct latent classes of CAM use emerged: 1) "Low-dose supplement users" (40 %), who used only common nutritional supplements; 2) "Vitamin/mineral supplement users" (39 %), using an abundance of supplements in addition to other practices; 3) "Mind-body medicine users" (12 %), with near-universal use of supplements, mind-body medicine techniques, and massage; and 4) "Multi-modality high-dose users" (9 %), who were highly likely to use nearly all types of CAM. Predictors of membership in classes with substantial CAM use included younger age, more education, higher income, Jewish religion, ideal body mass index, higher fruit and vegetable intake, higher levels of physical activity, receipt of adjuvant chemotherapy, and prior use of oral contraceptives. Conclusions LCA identified important subgroups of breast cancer patients characterized by varying degrees of complementary therapy use. Further research should explore the reproducibility of these classes and investigate the association between latent class membership and breast cancer outcomes.